Management science/operations research : a strategic perspective - Bell, Peter C. (Cincinnati, OH : South-Western College, 1999)
This book presents: An introduction to strategic management science; Models and model building; Analyzing sequential decisions; Thinking simultaneously; Simulating the future; ...
Keywords: Management; Strategic planning; Management science; Strategic planning; Operations research